Analysis of the Drying of Broccoli Florets in a Fluidized Pulsed Bed - Reyes-Salinas, A; Mahn-Osses, A (2012)
The effect of air temperature and flow rate, plate rotational speed, and initial broccoli particle size in a fluidized pulsed bed dryer on moisture content, diffusivity, antioxidant capacity, polyphenols content, and selenium concentration of conventional and selenium-enriched broccoli was investigated.Adjustment of the drying curves with the simplified constant diffusivity model was performed by intervals, in order to consider shrinkage, resulting in an average diffusivity equal to 4.9 E-09 (m 2/s), which is 82% higher than that observed in drying of broccoli in a tunnel dryer. In addition, the drying curves were adjusted to Page s model, resulting in R 2 values higher than 0.9.The conditions that maximize the antioxidant properties of conventional broccoli florets were air temperature of 60°C, air flow rate in the dryer inlet of 3 m/s, and initial particle size of 1 cm. The disk rotational speed had no statistically significant effect on the antioxidant properties in the range from 60 to 100 rpm. These operating conditions were then used to dehydrate selenium-enriched broccoli. The antioxidant properties in selenium-enriched broccoli after drying were comparable to those obtained for conventional broccoli. The conditions that minimized selenium loss were air temperature of 53°C and air flow rate of 2 m/s. © 2012 Copyright Taylor and Francis Group, LLC.